DEVELOPMENT OF NEW INDEX FRAMEWORK TO EVALUATE SAFETY PERFORMANCE LEVEL USING PROXIMITY TO TARGET APPROACH FOR OIL AND GAS INDUSTRY - THANGARAJAH, JEGHAN (2023)
At present, a dedicated safety index framework for monitoring and evaluating the safety performance of oil and gas fields has yet to be established. Ensuring a high level of safety performance is of utmost importance in the oil and gas industry due to its inherently hazardous nature.